2010
DOI: 10.1111/j.1468-0297.2010.02379.x
|View full text |Cite
|
Sign up to set email alerts
|

Trade‐induced Learning and Industrial Catch‐up

Abstract: This article develops a model of trade-induced learning whereby both domestic and cross-border learning externalities could drive long-run growth. This framework is used to synthesise the emerging empirical evidence, revealing how trade-induced learning could underpin the mechanics behind trade and growth in at least three important ways: first, trading matters, as firms might be able to increase their productivity due to export and import linkages with buyers and suppliers; second, whom you trade with matters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 111 publications
1
6
0
Order By: Relevance
“…It is worth noting that this result is remarkable since we are already controlling for some other well-known determinants of high-tech exports such as FDI, investment and human capital. Note that this result is in line with a broader literature reporting that it matters which countries you trade or interact with (Baliamoune-Lutz, 2019;Brambilla et al, 2012;Mendoza, 2010;Pahl & Timmer, 2020).…”
Section: T a B L E 2 The Impact Of Gvc Participation On High Technolo...supporting
confidence: 91%
“…It is worth noting that this result is remarkable since we are already controlling for some other well-known determinants of high-tech exports such as FDI, investment and human capital. Note that this result is in line with a broader literature reporting that it matters which countries you trade or interact with (Baliamoune-Lutz, 2019;Brambilla et al, 2012;Mendoza, 2010;Pahl & Timmer, 2020).…”
Section: T a B L E 2 The Impact Of Gvc Participation On High Technolo...supporting
confidence: 91%
“…It is essential to give a word of caution regarding the limitations of this study, which is the absence of a clear distinction of the effects of intermediate inputs. The latter, especially in the case of labour productivity, would add more precision to the analysis, as studies have shown that access to cheaper imported inputs can raise productivity via learning, variety, and quality effects (Mendoza, 2010). Further exploration on the empirical part should take into account possible interactions of the main regressors with dummies proxying low, medium and high tech and R&D expenditure to assess the temporal effects on actual domestic industrial upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence gives us the intuition that, to completely understand the scope of learning-by-exporting effects, we should introduce a spatial dimension of trade to the analysis (Mendoza, 2010;Segarra-Blasco et al, 2022;Tse et al, 2017). Due to the characteristics of our data, we cannot identify spatial learning-by-exporting such as in Segarra-Blasco et al (2022).…”
Section: Hypothesesmentioning
confidence: 95%